2022
DOI: 10.1002/fsn3.3053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of white mulberry powder fortification on antioxidant activity, physicochemical, microbial and sensorial properties of yogurt produced from buffalo milk

Abstract: The objective of this study was to investigate the effects of sun‐dried white mulberry fruit powder (WMFP) at addition levels of 2%, 4%, and 6% for enhancing nutritional value and improving the quality of yogurt during refrigerated storage. Results showed that the highest (p < .05) antioxidant activity of 54.53 ± 0.15% was observed in 6% WMFP‐added yogurt samples. Highest pH of 4.53 ± 0.08 was observed in control. Significantly highest (p < .05) acidity (1.12 ± 0.02%) was recorded in the yogurt with 6% WMFP‐ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Before sensory evaluation, samples were taken out from the refrigerator and served to panelists immediately (Kaur & Riar, 2020 ). The ratings were presented on a 9‐point hedonic ranking scale with the following score expressions: 1 = highly dislike, 2 = dislike very much, 3 = rather dislike, 4 = dislike a little, 5 = neither like nor dislike, 6 = quite like, 7 = rather like, 8 = like a lot, 9 = like very much (Sheikh et al, 2022 ). Yogurt sensory parameters were evaluated by appearance, fermented odor, texture, taste quality, and overall acceptance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before sensory evaluation, samples were taken out from the refrigerator and served to panelists immediately (Kaur & Riar, 2020 ). The ratings were presented on a 9‐point hedonic ranking scale with the following score expressions: 1 = highly dislike, 2 = dislike very much, 3 = rather dislike, 4 = dislike a little, 5 = neither like nor dislike, 6 = quite like, 7 = rather like, 8 = like a lot, 9 = like very much (Sheikh et al, 2022 ). Yogurt sensory parameters were evaluated by appearance, fermented odor, texture, taste quality, and overall acceptance.…”
Section: Methodsmentioning
confidence: 99%
“…The total phenolic content (TPC) of yogurt samples was determined by the Folin–Ciocalteu assay according to the method of Sheikh et al ( 2022 ). A gallic acid solution with concentrations of 0–100 μg/mL was used to construct the calibration curve and was treated in the same way as the sample solutions.…”
Section: Methodsmentioning
confidence: 99%
“…The GRAS probiotic strains are shown in Figure 1 . For food, the human‐derived probiotic strains are preferred because only such strains can properly colonize and remain viable in the human gastrointestinal tract without imparting any toxic effect on human body (Keservani et al, 2017 ; Sheikh et al, 2023 ).…”
Section: Selection Criteria For Probioticsmentioning
confidence: 99%
“…In this context, Wajs et al ( 6 ) suggested that yoghurts enriched with natural additives are more valuable, particularly with respect to health-promoting constituents’ content, such as phenolic compounds, fibre, essential vitamins, minerals, and fatty acids. Thus, many natural additives, such as date palm spikelets ( 25 ), moringa seed ( 26 ), cornelian cherry paste ( 27 ), grape seeds ( 28 ) and argel leaf ( 29 ) extracts, mulberry leaf and fruit powder ( 30 , 31 ), spearmint and lemongrass essential oils ( 32 ), lentil flour ( 33 ), and different types of fibres ( 34 ), have been incorporated in yoghurt formulation. The benefits of these and many other natural additives, usually added to yoghurt to serve a particular purpose, were discussed in a recent review ( 4 ).…”
Section: Introductionmentioning
confidence: 99%